DAMPAK PENERAPAN PERATURAN PEMERINTAH NOMOR 34 TAHUN 2016 (Studi Kasus di Kantor Pelayanan Pajak Pratama Kepanjen) - Stefani Yesia Nindy H; Ferry Irawan (Universitas Pamulang, 2018)
Abstract This study is conducted to find out the impact of Government Regulation number 34 of 2016 (PP 34 of 2016) implementation on final-income tax of transferring of land and/or building, and the number of tax payers who apply tax-remittance-letter validation of income tax. Data used in this study is taken from Kepanjen Tax Office. We collect tax revenue data for 56 weeks. To analyze the data, we use trend analysis and paired-test throughout F-test. The result shows that thax revenue tend to decrease although the number is not significant. Paired-test shows that there is no difference before and after the implementation of PP 34 of 2016 both in tax revenue and validation appeal. Keywords: PP 34 of 2016, final income tax